Biological Samples In Biomedical And Genetic Research: What Are The Ethical Parameters? - Fuentes Delgado, Duilio (2015)
The aim of this paper is to promote a regulatory for biological materials in biomedical and genetic research. Biobank 's role as an institution responsible for the custody and security of the stored materials, safeguarding the interests of donors and control the use and disposal of samples and results are detailed. Also, the biobanks must respect the intimacy and the privacy of individuals, the identity of suppliers and consent that should give the hoarder institution for eventual storage or subsequent use. When you plan the storage of human biological samples for future research, researchers should clearly state the following: a) Justification as to the need and opportunity for future use; b) Consent subject donors of biological material, allowing storage c) Submission for approval of a research ethics committee. In the final reflections establishes the need for the presence of the State in regulating research with biological and genetic samples to ensure a technical, bioethical and l